26.3k views
5 votes
X=−2 x=−1 x=1 6(0.5x−1.5)+2x=−9−(x+6) x = − 2 – 6 ( 0.5 x − 1.5 ) + 2 x = − 9 − ( x + 6 ) x = − 1 – 6 ( 0.5 x − 1.5 ) + 2 x = − 9 − ( x + 6 ) x = 1 – 6 ( 0.5 x − 1.5 ) + 2 x = − 9 − ( x + 6 ) 4(0.5x−2)+3x=−14−(x+6) x = − 2 – 4 ( 0.5 x − 2 ) + 3 x = − 14 − ( x + 6 ) x = − 1 – 4 ( 0.5 x − 2 ) + 3 x = − 14 − ( x + 6 ) x = 1 – 4 ( 0.5 x − 2 ) + 3 x = − 14 − ( x + 6 ) 8(0.5x−3)+4x=−9−(x+6)

User Jedwards
by
4.8k points

1 Answer

5 votes

Given:

Three equations are


6(0.5x-1.5)+2x=-9-(x+6)


4(0.5x-2)+3x=-14-(x+6)


8(0.5x-3)+4x=-9-(x+6)

Three solutions are
x=-2,x=-1,x=1.

To find:

The solution of each equation from the given solutions.

Solution:

We have,


6(0.5x-1.5)+2x=-9-(x+6)

Using distributive property, we get


3x-9+2x=-9-x-6


5x-9=-15-x

Isolate variable terms.


5x+x=-15+9


6x=-6

Divide both sides by 6.


x=-1

Similarly,


4(0.5x-2)+3x=-14-(x+6)


2x-8+3x=-14-x-6


5x-8=-20-x


5x+x=-20+8


6x=-12


x=-2

Now,


8(0.5x-3)+4x=-9-(x+6)


4x-24+4x=-9-x-6


8x-24=-15-x


8x+x=-15+24


9x=9


x=1

Therefore, the solutions of given equations
6(0.5x-1.5)+2x=-9-(x+6),
4(0.5x-2)+3x=-14-(x+6) and
8(0.5x-3)+4x=-9-(x+6) are x=-1, x=-2 and x=1 respectively.

User Thiyaneshwaran S
by
4.9k points